Quantification of the collagen fibers of healthy and neoplastic mammary tissue in cats by the Picrossirius Red histochemical method - Jorge, Mariana Fernandes; Patrocínio, Ana Cláudia; Hataka, Alessandre; Sequeira, Júlio Lopes (Brazilian Journal of Veterinary Pathology, 2021)
Although feline mammary carcinoma is not the most prevalent among the species, its aggressive behavior represents alow life expectancy, compared with most undifferentiated types of breast cancer. Tissue stiffness induced by the accumulationof collagen fibers is related to a risk factor for carcinogenesis in healthy women and aggressiveness in those with breast cancer,which can also occur in cats. The objective of this work is to identify the relationship between stromal collagen density andaggressiveness of mammary carcinoma in cats, according to the peripheral and central tissue distribution by the Picrossirius Redhistochemical method. Image.J® and MatLab® software were used for digital image processing. The mean values of kurtosisand entropy attributes were grouped into a control group, and low and high-grade carcinoma groups, analyzed with one-wayANOVA and Bonferroni’s multiple comparison test (p